Nigerian Broadcast Stations on Cable Networks: Navigating the Entry, Sustenance and Exit Triad - Obukoadata, Presly Ogheneruke; Usiwo Ogerugba, Isaac (UIR Press, 2025)
The Nigerian broadcasting industry has been facing significant challenges for 33 years, despite leveraging cable networks to improve broadcast quality. This study aims to identify the factors that influence their ability to enter and exit cable networks, explore the factors that affect their effectiveness, and assess their current condition on cable networks. This study relied on normative theories that provide guidelines for the media to operate in a way that best serves society. The theories include public interest, freedom of expression, and economic efficiency, as canvassed by authoritarian, liberation, and social responsibility theories. The methodology used in this study was survey research of media practitioners, with a sample size of 385, a questionnaire research instrument, and the use of simple percentages for data analysis. The study found that several factors, such as regulatory frameworks, market structures, and technological infrastructures influence the Nigerian broadcast industry's success on cable networks. To promote the industry's growth, the regulatory framework needs to be more transparent, the market structure needs to be more competitive, and the technological infrastructure needs to be more developed. To make Nigerian broadcast stations succeed, they need to focus on improving content quality, fostering strategic collaborations, and creating a competitive landscape. Furthermore, specific policy adaptations should be made to help Nigerian broadcast stations keep up with industry trends and improve the quality of their content.